SAT-LB38 Clinical Features, Treatment and Prognosis of Primary Bilateral Macronodular Adrenal Hyperplasia Compared With Unilateral Adrenal Cortisol-Secreting Adenoma: Analysis of 46 Chinese Cases - Zhang, Qian (J Endocr Soc, 2020)
Objectives: Primary bilateral macronodular adrenal hyperplasia (PBMAH) is a rare condition of Cushing’s syndrome (CS) characterized by benign bilateral enlarged adrenal masses. The aim of this study is to analyze clinical features, individualized treatment and prognosis of PBMAH. Methods: Clinical data of 46 patients with PBMAH were retrospectively analyzed compared with 205 patients with unilateral adrenal cortisol-secreting adenoma (UAA), including general information, cortisol evaluations, treatments and prognosis. Results: PBMAH were more frequently found in male, the average age at diagnosis was (52.1±8.7) years; most patients visited hospital due to incidentally findings of bilateral adrenal lesions; had a higher proportion of subclinical CS. The PBMAH cases showed significantly lower levels of basal cortisol, LDDST suppressed cortisol, and HDDST suppressed cortisol than the UAA cases (452.6 ± 183.3 vs. 578.7 ± 166.4 nmol/L, P = 0.003; 394.5 ± 298.9 vs. 549.2 ± 217.7 nmol/L, P= 0.002; 397.3 ± 282.3 vs. 544.3 ± 187.6 nmol/L, P =0.003). Similarly, the PBMAH cases had significantly lower levels of basal 24-h UFC, LDDST suppressed 24-h UFC, and HDDST suppressed 24-h UFC than the UAA patients (1144.4 ± 1048.1 vs. 1674.9 ± 1520.4 nmol/24h, P = 0.032; 1157.3 ± 1483.5 vs. 1940.1 ± 1360.9 nmol/24h, P = 0.003; 1256.4 ± 1767.0 vs. 1969.9 ± 1361.7 nmol/24h, P = 0.011). Compared PBMAH group with UAA group, there were statistically significant differences in the percentage change of cortisol (absolute value after suppressed over the basal value) during LDDST (73.01% ± 39.33% vs. 96.13% ± 31.59%, P =0.001) and during HDDST (73.90% ± 38.53% vs. 96.58% ± 28.79%, P=0.001); and there were statistically significant differences in the percentage change of 24-h UFC during LDDST (90.11% ± 79.60% vs. 134.47% ± 131.26%,P =0.045) and during HDDST (100.05% ± 89.59% vs. 143.75% ± 98.12%, P =0.017). The 24-hour continuous plasma ACTH and cortisol monitoring directly and thoroughly revealed the heterogeneity of hormone secretion of PBMAH cases. Among the 18 PBMAH cases with subclinical CS, 11 only received drug symptomatic treatment; 6 underwent unilateral adrenalectomy on the larger side; 1 not relieved well after unilateral adrenalectomy, then received resection of the contra-side. Among the 28 PBMAH cases with CS, 6 refused surgery because of economic reasons and just received symptomatic drugs treatment with bad prognosis; 15 underwent unilateral adrenalectomy on the larger side; 7 not relieved well after unilateral adrenalectomy, then conducted resection of the contra-side, and at last treated with glucocorticoid replacement obtained good prognosis. Conclusions: PBMAH is often associated with a relatively low degree of cortisol autonomous secretion. It is necessary to choose a specific therapy plan to alleviate the high cortisol state according to the individualized hypercortisolemia condition.